Preemptive interleukin‐6 blockade in patients with COVID‐19 (2020)
Excessive interleukin-6 signaling is a key factor contributing to the cytokine release syndrome implicated in clinical manifestations of COVID-19. Preliminary results suggest that tocilizumab, a humanized monoclonal anti-interleukin-6 receptor antibody, may be benefcial in severely ill patients, but no data are available on earlier stages of disease. An anticipated blockade of interleukin-6 might hypothetically prevent the catastrophic consequences of the overt cytokine storm. We evaluated early-given tocilizumab in patients hospitalized with COVID-19, and identifed outcome predictors. Consecutive patients with initial Sequential-Organ-Failure-Assessment (SOFA) score < 3 fulflling pre-defned criteria were treated with tocilizumab. Serial plasma biomarkers and nasopharyngeal swabs were collected. Of 193 patients admitted with COVID-19, 64 met the inclusion criteria. After tocilizumab, 49 (76.6%) had an early favorable response. Adjusted predictors of response were gender, SOFA score, neutrophil/lymphocyte ratio, Charlson comorbidity index and systolic blood pressure. At week-4, 56.1% of responders and 30% of non-responders had cleared the SARS-CoV-2 from nasopharynx. Temporal profles of interleukin-6, C-reactive protein, neutrophil/lymphocyte ratio, NT-ProBNP, D-dimer, and cardiac-troponin-I difered according to tocilizumab response and discriminated fnal in-hospital outcome. No deaths or disease recurrences were observed. Preemptive therapy with tocilizumab was safe and associated with favorable outcomes in most patients. Biological and clinical markers predicted outcomes.